Africa and The Decline of The Democracy Debate - Salih, Mohamed (Afrika Tanulmányok / Hungarian Journal of African Studies, 2021)
The debate on the decline of democracy is not new. It can be traced to the period between the First and Second World Wars, and it resurfaced during the 1970s, followed by the most spectacular democratic resurgence in human history. This lecture focuses on the current debate on the decline of democracy and downward trends in major democracy assessment indices. Africa is among the three least democratic world regions, with 42% of African countries currently designated as not free. Measuring the decline or rise of democracy only by the performance of institutional politics does not provide a complete picture of the issue. Institutional politics does not account for the resilience and thriving new spaces where democratic vibrancy and civic engagement prevail. Examples from African countries demonstrate that democracy indices based on institutional politics alone do not account for alternative democratic spaces and practices. This paper is the edited version of the keynote speech delivered by the author at the 6th Pécs African Studies Conference under the theme “African Realities: Conflict and Cooperation”, September 23-24, 2021 – University of Pécs, Hungary.